Grounding Ecological Democracy: Semiotics and the Communicative Networks of Nature. (1st August 2021) - Romero, Javier; Dryzek, John S.
Developments in biosemiotics and democratic theory enable renewed appreciation of the possibilities for ecological democracy. Semiotics is the study of sign processes in meaning-making and communication. Signs and meanings exist in all living systems, and all living systems are therefore semiotic systems. Ecological communication can involve abiotic and biotic communication, including human language, facilitating an integration of politics and ecology in the form of ecological democracy encompassing communicative networks in nature and human society.